Erbium‐Ion‐Doped Tellurite Glasss Fibers and Waveguides — Devices and Future Prospective: PART I. (21st August 2013) - Joshi, Purushottam; Irannejad, Mehrdad; Zhao, Zhanxiang; Fernandez, Toney; Richards, Billy; Jose, Gin; Jha, Animesh; Lousteau, Joris
Abstract : This review article focuses on the suitability of Er 3+ ‐doped tellurium oxide glass for optical amplification in fiber, waveguides and as a component for optical integration to meet the emerging demand for broadband and fiber‐to‐home networks. The importance of the glass structure, in the context of Er 3+ ‐ion spectroscopy, is emphasized for dissolving large concentrations of dopant ions. The spectroscopic methodologies involved in maximizing the gain per unit length of Er 3+ ‐doped fiber is explained. In Part II of this study, a review of how the fiber gain data was then employed to engineer amplification in waveguides, which can be integrated with semiconductor pump sources, is presented.